Chronic Apical and Nonapical Right Ventricular Pacing in Patients with High-Grade Atrioventricular Block: Results of the Right Pace Study. (22nd May 2018) - Muto, Carmine; Calvi, Valeria; Botto, Giovanni Luca; Pecora, Domenico; Porcelli, Daniele; Costa, Alessandro; Ciaramitaro, Gianfranco; Airò Farulla, Riccardo; Rago, Anna; Calvanese, Raimondo; Baratto, Marco Tullio; Reggiani, Albino; et al.
Abstract : Objective . The aim of the study was to compare the two approaches to chronic right ventricular pacing currently adopted in clinical practice: right ventricular apical (RVA) and non-RVA pacing. Background . Chronic RVA pacing is associated with an increased risk of atrial fibrillation, morbidity, and even mortality. Non-RVA pacing may yield more physiologic ventricular activation and provide potential long-term benefits and has recently been adopted as standard procedure at many implanting centers. Methods . The Right Pace study was a multicenter, prospective, single-blind, nonrandomized trial involving 437 patients indicated for dual-chamber pacemaker implantation with a high percentage of RV pacing. Results . RV lead-tip target location was the apex or the interventricular septum. RVA (274) and non-RVA patients (163) did not differ in baseline characteristics. During a median follow-up of 19 months (25th–75th percentiles, 13–25), 17 patients died. The rates of the primary outcome of death due to any cause or hospitalization for heart failure were comparable between the groups (log-rank test, p = 0.609 ), as were the rates of the composite of death due to any cause, hospitalization for heart failure, or an increase in left ventricular end-systolic volume ≥ 15% as compared with the baseline evaluation (secondary outcome, p = 0.703 ). After central adjudication of X-rays, comparison between adjudicated RVA (239 patients) and non-RVA (170 patients) confirmed the absence of difference in the rates of primary (p = 0.402 ) and secondary (p = 0.941 ) outcome. Conclusions . In patients with indications for dual-chamber pacemaker who require a high percentage of ventricular stimulation, RVA or non-RVA pacing resulted in comparable outcomes. This study is registered with ClinicalTrials.gov (identifier:NCT01647490 ).